A design of adaptive user interface to cater the learners' diversity in online learning for blended-learning / Roslan Sadjirin …[et al.] - Sadjirin, Roslan; Nordin, Noli Maishara; Noradzan, Haslinda; Ahmad Zaini, Azniza; Canda, Roger (2014)
Blended learning is a method that involved face-to-face and guided non-face-to-face stages of teaching and learning practices. Face-to-face teaching and learning is a common practice long before computers and internet technology come into existence. On the other hand, guided non-face-to-face teaching and learning is a practice that employed and used the computer and internet technology to deliver teaching and stimulate the learning process of students without seeing in formal meeting between students and lecturers. However, as long as the guided non-face-to-face is concern, the diversity of the students or learners need to be put into consideration. Everyone has different ways in cognitive learning style. Each learner possesses a unique way in acquiring, memorising, manipulating and understanding knowledge and information. Therefore, this paper describes the design of intelligent adaptive user intelface for tutorial package to cater the diversity of learners in online learning practices. A mamdani style of fuzzy logic inference approach is employed to design the adaptivity of the user interface for user model.